HISTOLOGICAL ASSESSMENT OF BACTERIAL DENSITY AND INFLAMMATORY CELL INFILTRATE IN PIGS WITH HELICOBACTER SPP.-ASSOCIATED CHRONIC GASTRITIS - Pejchinovska, Natasha; Karabolovski, Nikola; Dodovski, Petar; Dameski, Pance; Zdraveski, Igor; Avramov, Aleksandar; Angelovska, Maja; Hristovska, Talija; Ristevski, Mimi (Horizons - International Scientific Journal, 2020)
The aim of this study was to determine the association between Helicobacter spp.: Helicobacter pylori-like organisms (HLO) and Gastrospirillum-like organisms (GLO) density and severity of chronic inflammatory infiltrate in the pyloric mucosa of pig’s stomach. A total of 120 fragments of pyloric mucosa were included in the study. It was seen that HLO was found mostly in grade 2 of density, while GLO in grade 1 of density. Chronic inflammatory infiltrate was estimated mostly as grade 2 in HLO positive samples and grade 1 in GLO positive samples. Regardless of the bacterial density, we found that grade of chronic inflammatory infiltrate was higher in HLO positive samples than GLO positive samples.